The image of islam in US print media discourse: The New York Times - ACIM RACHID (Faculté des Lettres et Sciences Humaines, Béni Mellal - Doctorat ou Doctorat National, 2014)
This research is divided into two major parts: The first is theoretical and the second is empirical. In the first place, we have attempted to provide a theoretical background by examining the different notions of discourse analysis such as discourse, text, ideology, pragmatics and so on. We have also traced up the evolution of the newspaper and put into focus its basic constituents like News, Editorials and Op-Eds. Media studies, along with rhetoric have also been addressed, with the intention of probing into how the media influence the public opinion. Being the subject of the study, the New York Times (and henceforth NYT) is introduced with all its basic components. Issues of bias and objectivity are questioned from the very beginning to show how hard or troublesome an experience might be to judge or even assess the paper ideological line. After that, the research focuses on stereotyping Islam and the rise of Orientalism. This latter theory is about the way the West has created the myth of the Orient in its discourse, the intentional or un-intentional tendency to otheri-ze or exoticize some minority groups like Muslims and Arabs. Next, the research points to the contribution made by Shaheen (2001) with his treatise Reel Bad Arabs. In the meantime, it examines the roots of the problem between the world of Islam and the Judeo-Christian West. The theoretical part concludes with an overview on the earlier research done on the image of Islam in the print media discourse.
Keywords: discourse analysis; newspaper; media influence; New York Times; bias; objectivity; Orientalism; stereotyping; minority groups; image of Islam; الإنجليزية